DETECTION OF MMP3 BY IN SITU – HYBRIDIZATION TECHNIQUE IN ORAL SQUAMOUS CELL CARCINOMA - Mohammad, Dena N.; Garib, Balkees T.; Abdul–Majeed, Ban A. (European Scientific Journal, ESJ, 2014)
Background: MMP3 is a member of zinc-dependent proteinases family that is associated with extracellular matrix degradation in physiological and pathological conditions such as tumor metastasis. Hence, they form part of the invasive machinery of cancer cells. Objectives: The objective of this study is to evaluate MMP3 signals (by in situ- hybridization technique in the cancer cells and the surrounding stroma, whether it is at an early or deep invasive site) in oral squamous cell carcinoma, and correlate such expression with histopathological grading. Materials and Methods: MMP3 signals were identified by ISH technique in paraffin blocks of 40 oral squamous cell carcinoma and in 10 normal oral mucosa. Chi- square test and Pearson’s correlation were applied for analysis. P < 0.05 was considered statistically significant. Results: In normal oral mucosa, the stromal cells displayed MMP3 signals while surface epithelia did not. In oral squamous cell carcinoma, 18 cases (45%) did not reveal any signals (negative cases). Positive signals expression (whether in cancerous or stromal cells ) were seen in 22 OSCC (55%), with the following localization; in cancerous cells only (4.5% ) , in stromal cells only (18.1%) and in both of them ( 77.2%). Both early and deep invasive lesions illustrated great combined cancerous and stromal signals (52.6% and 33.3% respectively). Regarding signals localization and their distribution with respect to the depth of the lesion, significant relation was noted with histopathological grading. Early invasive lesions had more superficial stromal signals of 31.5%, while deep invasive lesions revealed great combined stromal signals of 33.3% .Conclusion: MMP3 signals were recognized in more than half of the sample of 55%, and are more frequently seen with combined cancer and stromal localization in early invasive lesion which is significantly related to histopathological grading.